O desenvolvimento histórico do conceito de energia : seus obstáculos epistemológicos e suas influências para o ensino de física - Lino, Alex (2016)
This paper aimed, as its main goal, the epistemological construction of the concept of energy, through a study about its epistemological obstacles and their relation with the alternative conceptions of students on the same concept. On the basis of epistemological theories of Gaston Bachelard and Jean Piaget, it was discussed the possible relations between the historical construction and cognitive construction of a certain knowledge. Such epistemologies suggest that there is a parallelism between these two strands. It was also analyzed if the difficulties found in the history of the construction of the concept of energy may be compared to the ones faced by students. In order to reach this goal, it was necessary a detailed study of the history concerning the development of the concept of energy, aiming to highlight the mechanisms that guide the possibility of its development, besides clarifying which were its historical obstacles. By an analysis about the alternative conceptions of students regarding to the concept of energy, which were previously analyzed by other authors, it was possible to verify that there are mistakes, which commonly and frequently, students present, independently of their different levels of education, culture or contexts, such as their misunderstanding between the concepts of force and energy, or yet, their belief that energy must have material characteristics. It was also verified that the difficulties found in the historical study of the concept presented similarities to the alternative conceptions of students. Bearing this in mind, it was possible to identify four epistemological obstacles related to the concept of energy: 1) The notion of force as obstacle to the concept, 2) the notion of gain without losses as obstacles to its conservation, 3) the restrictions to particular phenomena as obstacles to its generalization, 4) and the notion of substancialization. It was also identified how these obstacles could be surpassed or overcome by the historical study. Such construction enabled to identify the determined mechanisms of overcoming of epistemological obstacles, which may be used in physics teaching with the same intention of undo the obstacles badly settled.